The Construction of an Aircraft Control Multilayer Network and Its Robustness Analysis - Guangjian Ren; Ming Zhang; Yushuai Guo (Journal of Advanced Transportation)
When aircraft are flying along the routes, their states present diversity and complexity. To clarify the control or monitoring relationship between air sectors and aircraft in the airspace and to promote reliability and efficiency of air traffic control (ATC), in this paper, an aircraft control multilayer network (ACMN) model is built by considering the air sector network (ASCN) and the aircraft state network (ASTN). The characteristics of ACMN are studied based on complex network theory. Simultaneously, according to the multilayer characteristics of ACMN and the relative entropy theory, a robustness analysis method is proposed. Results show that the proposed method is applicable for evaluating the structural stability and robustness of ACMN and is effective in improving the efficiency of ATC. It can also provide a new idea for the robustness research of multilayer networks.